2018
DOI: 10.1155/2018/6154382
|View full text |Cite
|
Sign up to set email alerts
|

A Case of a Pregnant Woman with Thrombosis in an Artificial Aortic Valve Resulting in Severe Cerebral Hemorrhage in the Newborn

Abstract: Many patients, after artificial valve replacement surgery, receive warfarin anticoagulant therapy. However, it has been reported that warfarin administration during pregnancy can cause fetal teratogenicity. With reference to this case, we will discuss how warfarin administration in mid-pregnancy caused severe cerebral hemorrhage in the newborn child. The 36-year-old patient in this case underwent aortic valve replacement surgery when she was 11 years old; this requires the continued use of warfarin after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…5 Except for its teratogenic risk in the first trimester, warfarin is a comparatively safe anticoagulation choice because of its lower thrombosis rate. In our literature review, Kamei et al 12 reported a case of thrombosis formation during heparin administration. After increasing the dosage of heparin and restarting warfarin for 2 weeks, the thrombus disappeared at the 24th gestational week.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…5 Except for its teratogenic risk in the first trimester, warfarin is a comparatively safe anticoagulation choice because of its lower thrombosis rate. In our literature review, Kamei et al 12 reported a case of thrombosis formation during heparin administration. After increasing the dosage of heparin and restarting warfarin for 2 weeks, the thrombus disappeared at the 24th gestational week.…”
Section: Discussionmentioning
confidence: 89%
“…In our literature review, Kamei et al. 12 reported a case of thrombosis formation during heparin administration. After increasing the dosage of heparin and restarting warfarin for 2 weeks, the thrombus disappeared at the 24th gestational week.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations